The tort of interference : trade unions / Aznan Nawani - Nawani, Aznan (Faculty of Law, 1982)
A violation of legal right corrisitted knowingly is a couse of action, and that it is a violation of legal right to interfere with contractual relations recognised by law if there be no justification for the interference. Acts of a third party lawful in themselves do not constitute actionable interference with contractual rights merely because they bring about a breach of contract, even if they were done with the object and intertion of bringing about such a breach.